2008
DOI: 10.1007/s00264-008-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted versus conventional cemented total knee prostheses alignment accuracy and micromotion of the tibial component

Abstract: We evaluated the influence of CT-free or CT-based computer assisted orthopaedic surgery (CAOS) on the alignment of total knee prostheses (TK) and micromotion of tibial components. This randomised study compared 19 CTfree, 17 CT-based CAOS TK, and a matched control group of 21 conventionally placed TK. Using Roentgen stereophotogrammetric analysis (RSA) the migration was measured. The alignment and component positions were measured on radiographs. No significant difference in leg and tibial component alignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…Although many studies have confirmed this theory [1,3,9,24,39], others have shown that there is no difference in orientation or alignment of the femoral or tibial components than that achieved by conventional methods [12,22,23,42]. When evaluating the published reports on navigation knee arthroplasty, two important factors limit comparisons among clinical series.…”
Section: Alignmentmentioning
confidence: 87%
“…Although many studies have confirmed this theory [1,3,9,24,39], others have shown that there is no difference in orientation or alignment of the femoral or tibial components than that achieved by conventional methods [12,22,23,42]. When evaluating the published reports on navigation knee arthroplasty, two important factors limit comparisons among clinical series.…”
Section: Alignmentmentioning
confidence: 87%
“…In a former study by Van Strien et al [31], the CAOS system was evaluated using postoperative radiographs and CT scans as well as RSA. The protocol was approved by the institutional medical ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…The number of total knee arthroplasties (TKAs) performed worldwide is growing considerably, and for the past few years new computer-assisted navigation systems have been developed to help orthopaedic surgeons achieve more accurate prosthetic alignment [1][2][3][4][5]. The PLEOS knee system (Tornier®, Saint-Ismier, France) is image-free and creates the mechanical axis of the femur for femoral component positioning using the "rotational method" [6,7].…”
Section: Introductionmentioning
confidence: 99%